Implementasi pelayanan kesehatan peduli remaja di Puskesmas - Heraini Heraini; Achmad Rifai; Endang Maryanti (Fakultas Kesehatan Masyarakat Universitas Prima Indonesia, 2022)
The Youth Care Health Service Program is a model of health services both physical and mental, aimed at adolescents. This research aims to find out the implementation of the PKPR program at the Medan City Health Center. This research is a qualitative descriptive study held in August to September 2020. The informants in this study consisted of 11 informants. Data collection uses observation, interviews, and documentation. Data is analyzed by reducing data, presenting data and drawing conclusions. The results of the study are known that there are 3 human resources who have received training. Special allocation funds are limited. Facilities and Infrastructure are available, but join the IMS VCT space. The Decree of the Head of the Puskesmas has been made but the officers who enter the Team have not all received training from the Health Office. Planning of PKPR activities at puskesmas is often adjusted to POA BOK. Organizing in accordance with Permenkes number 31 of 2019 concerning Puskesmas Information System. The implementation of PKPR activities at puskesmas Often does not cover all fostered school teenagers and adolescents outside the school. Officers provide health advice / information in accordance with the health problems found. Recording and reporting are done, but the reporting format is often variable. The result of the implementation of the PKPR program is that the number of teenagers who take advantage of this PKPR program has not increased. Based on the results of this study, it is expected that it is necessary to improve the competence of PKPR officers, funding support, adequate infrastructure, planning and implementation of activities that reach adolescents inside and outside the school, increasing cooperation with related parties and monitoring and evaluation of activities by the Health Office every year